Lower Paleolithic bone tools from the 'Spear Horizon' at Schöningen (Germany). Issue 89 (December 2015) - Van Kolfschoten, Thijs; Parfitt, Simon A.; Serangeli, Jordi; Bello, Silvia M.
Abstract: The Lower Paleolithic locality of Schöningen 13 II-4 is famous for the discovery of wooden spears found amongst the butchered remains of numerous horses and other large herbivores. Although the spears have attracted the most interest, other aspects of the associated artifact assemblage have received less attention. Here we describe an extraordinary assemblage of 88 bone tools from the 'Spear Horizon.' This sample includes numerous long-bone shaft fragments (mostly of horse), three ribs used as 'retouchers' to resharpen flint tools, and a complete horse innominate that was used as an anvil in bipolar knapping. Most of the retouchers were prepared by scraping the diaphysis of fresh and dry long-bones. Technological analysis of the associated lithic assemblage demonstrates exhaustive resharpening to maintain functional cutting edges. Whereas the flint tools were brought to the site, curated, and maintained, the retouchers had a shorter use-history and were either discarded after a limited period or broken to extract marrow. Horse and bison metapodials with flaked and rounded epiphyses are interpreted as hammers used to break marrow bones. Several of the 'metapodial hammers' were additionally used as knapping percussors. These constitute the earliest evidence of multi-purpose bone tools in the archeological record. Our results highlight the advanced knowledge in the use of bones as tools during the Lower Paleolithic, with major implications for understanding aspects of non-lithic technology and planning depth in early hominins.